1991
DOI: 10.1089/neu.1991.8.193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Serotonin Antagonist, Opioid Antagonist, and TRH Analog for the Acute Treatment of Experimental Spinal Trauma

Abstract: The therapeutic efficacies of a serotonin antagonist (mianserin), an opioid antagonist (nalmefene), and a TRH analog (YM-14673) were compared in a well-characterized model of experimental spinal trauma in the rat. Injury was produced by the weight-drop method at T10 and confirmed by the disappearance of the somatosensory evoked response during the subsequent 15 minutes. Drug or vehicle treatments were administered randomly as a single intravenous bolus 15 minutes after injury. Functional outcome was blindly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…(C) A significant correlation was detected between lesion volume values obtained with the two methods (P < 0.05, regression ANOVA). a variety of experimental models of CNS trauma in a number of species (Akdemir et al, 1993;Arias MJ, 1987;Behrmann et al, 1994;Ceylan et al, 1990Ceylan et al, , 1992Faden, 1989Faden, , 1993Faden et al, 1981Faden et al, , 1990Fukuda et al, 1979;Puniak et al, 1991;Takami et al, 1991;Wang and Zhu, 1991). A small clinical study confirmed these beneficial effects in human spinal cord injury (Pitts et al, 1995).…”
Section: Figmentioning
confidence: 99%
“…(C) A significant correlation was detected between lesion volume values obtained with the two methods (P < 0.05, regression ANOVA). a variety of experimental models of CNS trauma in a number of species (Akdemir et al, 1993;Arias MJ, 1987;Behrmann et al, 1994;Ceylan et al, 1990Ceylan et al, , 1992Faden, 1989Faden, , 1993Faden et al, 1981Faden et al, , 1990Fukuda et al, 1979;Puniak et al, 1991;Takami et al, 1991;Wang and Zhu, 1991). A small clinical study confirmed these beneficial effects in human spinal cord injury (Pitts et al, 1995).…”
Section: Figmentioning
confidence: 99%
“…The disadvantage of opiate antagonists is the fact that they block the analgesic effects of endogenous or exogenous opiates. Therefore, TRH and analogs were thought to be more effective, by acting in vivo as partial physiologic opiate antagonists that spare analgesic systems [4,49,56,59,124]. Moreover, it was shown that TRH but not naloxone treatment starting 24 h and as late as 7 days after injury is effective in rats with severe neurologic impairment following SCI.…”
Section: Neuropeptidesmentioning
confidence: 99%
“…Thus, it is suggested that the duration of the effectiveness of late treatment with TRH on the neurologic impairment in rats with SCI is > 1 week, while the duration with naloxone is < 24 h [93]. In contrast to the neurologic recovery described by Faden et al for opioid antagonists [58] and TRH analogs [59], Puniak et al [124] found that none of the agents was effective in preserving the central gray matter or the white matter at the site of injury.…”
Section: Neuropeptidesmentioning
confidence: 99%
“…4 ± 6 Further, mianserin (5-HT2A antagonist) has been reported to be neuroprotective in acute spinal cord injuries. 7,8 Thus, 5-HT receptors may play a role in the pathological responses of axons to injury. However, in the absence of any previous evidence for 5-HT receptors existing on axons, most hypotheses regarding 5-HT mediated secondary axonal injury have focused on indirect mechanisms, such as posttraumatic ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, the mechanisms by which 5-HT causes secondary tissue damage, especially with axons, are not well understood. Most investigators have focused on the possible indirect eects of 5-HT, such as posttraumatic ischemia, and it has been demonstrated that some peripheral and central axon terminals have 5-HT autoreceptors.…”
mentioning
confidence: 99%